Resonant excitation during strong-field dissociative ionization - Alnaser, A. S.; Zamkov, M.; Tong, X. M.; Maharjan, C. M.; Ranitovic, P.; Cocke, C. L.; Litvinyuk, I. V. (My University, 2005)
We studied dissociative ionization of oxygen by intense femtosecond laser pulses with central wavelengths between 550 and 1800 nm. We measured kinetic energy release spectra and angular distributions of fragments resulting from symmetric dissociation of doubly charged molecular ions (O2+2→O++O+ channel). In the kinetic energy release spectra we identified a number of distinct excited states of the molecular ion. Angular distributions for all but one of those states were consistent with recollision excitation following single ionization of O2. For the remaining (B3Πg) excited state we observed a characteristic resonant dependence of its relative yield on the central optical frequency of the pulse, with the yield peaking at around 890 nm. This presents unambiguous evidence in support of importance of resonant excitation channels in strong field ionization of molecules.